2024
DOI: 10.1136/tsaco-2023-001286
|View full text |Cite
|
Sign up to set email alerts
|

Golf cart injuries have similar severity to all-terrain vehicle injuries in children: a multicenter comparison over a 5-year period

Henry L Chang,
Brian K Yorkgitis,
Lindsey B Armstrong
et al.

Abstract: BackgroundGolf carts (GCs) and all-terrain vehicles (ATVs) are popular forms of personal transport. Although ATVs are considered adventurous and dangerous, GCs are perceived to be safer. Anecdotal experience suggests increasing numbers of both GC and ATV injuries, as well as high severity of GC injuries in children. This multicenter study examined GC and ATV injuries and compared their injury patterns, resource utilization, and outcomes.MethodsPediatric trauma centers in Florida submitted trauma registry patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In their article, 1 the authors compare injury distribution, severity and outcome between children injured in all-terrain vehicle (ATV) and golf cart accidents across 10 Florida trauma centers. Their study demonstrated increasing incidence of pediatric golf cart-related trauma, a rise reported since the early 2000s by Watson et al 2 and our own institution, 3 with a corresponding increase in medical and regulatory interest.…”
mentioning
confidence: 99%
“…In their article, 1 the authors compare injury distribution, severity and outcome between children injured in all-terrain vehicle (ATV) and golf cart accidents across 10 Florida trauma centers. Their study demonstrated increasing incidence of pediatric golf cart-related trauma, a rise reported since the early 2000s by Watson et al 2 and our own institution, 3 with a corresponding increase in medical and regulatory interest.…”
mentioning
confidence: 99%